Cortical activation following chronic passive implantation of a wide-field suprachoroidal retinal prosthesis - Villalobos, Joel; Fallon, James; Nayagam, David; Shivdasani, Mohit; Luu, Chi; Allen, Penelope; Shepherd, Robert; Williams, Chris (IOP Publishing, 2014)
OBJECTIVE: The research goal is to develop a wide-field retinal stimulating array for prosthetic vision. This study aimed at evaluating the efficacy of a suprachoroidal electrode array in evoking visual cortex activity after long term implantation. APPROACH: A planar silicone based electrode array (8 mm × 19 mm) was implanted into the suprachoroidal space in cats (ntotal = 10). It consisted of 20 platinum stimulating electrodes (600 μm diameter) and a trans-scleral cable terminated in a subcutaneous connector. Three months after implantation (nchronic = 6), or immediately after implantation (nacute = 4), an electrophysiological study was performed. Electrode total impedance was measured from voltage transients using 500 μs, 1 mA pulses. Electrically evoked potentials (EEPs) and multi-unit activity were recorded from the visual cortex in response to monopolar retinal stimulation. Dynamic range and cortical activation spread were calculated from the multi-unit recordings. MAIN RESULTS: The mean electrode total impedance in vivo following 3 months was 12.5 ± 0.3 kΩ. EEPs were recorded for 98% of the electrodes. The median evoked potential threshold was 150 nC (charge density 53 μC cm(-2)). The lowest stimulation thresholds were found proximal to the area centralis. Mean thresholds from multiunit activity were lower for chronic (181 ± 14 nC) compared to acute (322 ± 20 nC) electrodes (P < 0.001), but there was no difference in dynamic range or cortical activation spread. SIGNIFICANCE: Suprachoroidal stimulation threshold was lower in chronic than acute implantation and was within safe charge limits for platinum. Electrode-tissue impedance following chronic implantation was higher, indicating the need for sufficient compliance voltage (e.g. 12.8 V for mean impedance, threshold and dynamic range). The wide-field suprachoroidal array reliably activated the retina after chronic implantation.
Keywords: blindness; retinal prosthesis; suprachoroidal; electrical stimulation